Keratosis follicularis spinulosa decalvans. - Chieco, P. (European Journal of Pediatric Dermatology, 2018)
Keratosis follicularis spinulosa decalvans is a dominant X-linked hereditary disorder thus affecting less severely females, but it can be autosomal dominant or more often sporadic. Its boundaries with other forms of keratosis follicularis atrophicans are not clear and there is overlapping with other diseases included in the group of lichen planopilaris, so that some Authors (2) proposed to unify all these forms with the name of lichenoid folliculitis. The disease starts from the first months of life with follicular keratosis of the face that then extends to other areas and is associated with inflammation of variable entity till formation of pustules (1) specially in the dominant autosomal form, that usually deteriorates at puberty with cicatricial alopecia, which is the hallmark of the disease. The treatment is poorly effective as shown by the proliferation of topical and systemic therapies.